Digitalisasi Manajemen Produksi dan Keuangan pada Usaha Kecil di Pangkalpinang, Kabupaten Bangka - Wahyudie, Ilham Ary; Afriansyah, Riki; Rodika, Rodika; Sukanto, Sukanto (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2024)
Small and Medium Enterprises (UKM) in Pangkal Pinang, Bangka, often need help managing production and finance due to limited application of information technology. To overcome the problems of managing production and finance, this community service activity was carried out to implement the